Plastic films in food packaging : materials, technology and applications - Ebnesajjad, Sina (Plastics Design Library., 2013)
The value of the groceries purchases in the USA is over 500 billion annually, most of which is accounted for by packaged foods. Plastic packaging of foods is not only ubiquitous in developed economies, but increasingly commonplace in the developing world, where plastic packaging is instrumental in decreasing the proportion of the food supply lost to spoilage. This new handbook is a combination of new material and updated chapters, chosen by Dr. Sina Ebnesajjad, from recently published books on this subject. Plastic Films in Food Packaging offers a practical handbook for eng.